PENGARUH KUALITAS DOKUMEN PELAKSANAAN ANGGARAN (DPA), AKURASI PERENCANAAN KAS, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PENYERAPAN ANGGARAN PADA KABUPATEN PONOROGO - Ilyana Khansa (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
This study aims to analyse the effect of Budget Implementation Document (DPA) Quality, Cash Planning Accuracy, and Human Resources Quality on budget absorption in Ponorogo Regency. This research uses quantitative descriptive method. The population in this study were 46 Regional Apparatus Organisations in Ponorogo Regency. Sampling using total sampling technique. The data used is primary data. The data was obtained by distributing questionnaires directly by visiting the OPD one by one. This study uses multiple linear regression analysis with the help of the SPSS version 25 application. The results of this study indicate that the first hypothesis that the quality of DPA affects budget absorption. The second hypothesis shows that cash planning accuracy affects budget absorption. The results of the third hypothesis show that the quality of human resources affects budget absorption. And the results of the fourth hypothesis show that the quality of DPA, cash planning accuracy, and the quality of human resources have a simultaneous effect on budget absorption.